If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7(x + 1) + -17 = 21 + 4 Reorder the terms: -7(1 + x) + -17 = 21 + 4 (1 * -7 + x * -7) + -17 = 21 + 4 (-7 + -7x) + -17 = 21 + 4 Reorder the terms: -7 + -17 + -7x = 21 + 4 Combine like terms: -7 + -17 = -24 -24 + -7x = 21 + 4 Combine like terms: 21 + 4 = 25 -24 + -7x = 25 Solving -24 + -7x = 25 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '24' to each side of the equation. -24 + 24 + -7x = 25 + 24 Combine like terms: -24 + 24 = 0 0 + -7x = 25 + 24 -7x = 25 + 24 Combine like terms: 25 + 24 = 49 -7x = 49 Divide each side by '-7'. x = -7 Simplifying x = -7
| 3b-33=0 | | 2x^2-600=0 | | 64x^2-69x-2=0 | | 14x=14x+9 | | 3x+4x-7=12 | | 10+2y=2(1x+5) | | 9x-7=5+8x | | 5(n+1)=45 | | 2x+16=4x+4 | | -9c+8=-37 | | 3+6x=36 | | 9x-10=3x+38 | | -6(x+2)-13=22+1 | | -2x=4x+20 | | 1.4-1.6(t+60)=4.6 | | N+3=x-1 | | 6-3*-.4=-18*-.4 | | 5x-3(1x-6)=2 | | 22/6 | | 3x=1+y | | -5(t+9)+4(2t+4)=2(t-8)+6 | | 11-8q=3q-19 | | 6k-25=7-9k | | 6n^2=12n+90 | | 4(4x+1)=116 | | 20x^2-92x-40=0 | | 8-(4n-5)=7-5n | | 7x+3=6x+9 | | 4t^2+19t+21=0 | | 0.12(y-5)+0.02y=0.10y-0.03(30) | | 5x+-4y=3 | | 4t-19t+21=0 |